Country specific predictions of the cost-effectiveness of malaria vaccine RTS, S/AS01 in endemic Africa. Issue 1 (3rd January 2017) - Galactionova, Katya; Tediosi, Fabrizio; Camponovo, Flavia; Smith, Thomas A.; Gething, Peter W.; Penny, Melissa A.
Highlights: RTS, S has the potential to substantially reduce malaria burden in children in endemic Africa. Adding RTS, S to routine malaria control is potentially highly cost-effective. At Pf PR2–10  > 10% predicted cost-effectiveness averages $136 per DALY averted. Under conservative assumptions predicted cost-effectiveness of RTS, S is, at most, doubled. Differences in country epidemiology and healthcare delivery result in substantial variation in predicted impact. Abstract: Background: RTS, S/AS01 is a safe and moderately efficacious vaccine considered for implementation in endemic Africa. Model predictions of impact and cost-effectiveness of this new intervention could aid in country adoption decisions. Methods: The impact of RTS, S was assessed in 43 countries using an ensemble of models of Plasmodium falciparum epidemiology. Informed by the 32 months follow-up data from the phase 3 trial, vaccine effectiveness was evaluated at country levels of malaria parasite prevalence, coverage of control interventions and immunization. Benefits and costs of the program incremental to routine malaria control were evaluated for a four dose schedule: first dose administered at six months, second and third - before 9 months, and fourth dose at 27 months of age. Sensitivity analyses around vaccine properties, transmission, and economic inputs were conducted. Results: If implemented in all 43 countries the vaccine has the potential to avert 123 (117; 129) million malaria episodes over the first 10 years. Burden averted averages 18, 413 (range of country median estimates 156–40, 054) DALYs per 100, 000 fully vaccinated children with much variation across settings primarily driven by differences in transmission intensity. At a price of $5 per dose program costs average $39.8 per fully vaccinated child with a median cost-effectiveness ratio of $188 (range $78–$22, 448) per DALY averted; the ratio is lower by one third - $136 (range $116–$220) - in settings where parasite prevalence in children aged 2–10 years is at or above 10%. Conclusion: RTS, S/AS01 has the potential to substantially reduce malaria burden in children across Africa. Conditional on assumptions on price, coverage, and vaccine properties, adding RTS, S to routine malaria control interventions would be highly cost-effective. Implementation decisions will need to further consider feasibility of scaling up existing control programs, and operational constraints in reaching children at risk with the schedule.